Sinergi Pendidikan Informal, Formal, dan Nonformal dalam Perspektif Pendidikan Islam - Saleh, Muhammad; Yahya, Muhammad Nur; Qasim, Muhammad (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Islamic education is a comprehensive process of human development that encompasses spiritual, moral, intellectual, and social dimensions. In practice, Islamic education is not conducted through a single educational pathway but is implemented through informal, formal, and nonformal education, which complement one another. This article aims to examine the concepts, roles, and forms of synergy of Islamic education within these three educational pathways in shaping a generation of Muslims who are faithful, knowledgeable, and possess noble character (akhlaq al-karimah). This study employs a qualitative approach using a library research method by analyzing various literature sources, including books, scholarly journals, and relevant regulations related to the national education system and Islamic education. The findings indicate that informal education within the family serves as the primary foundation for character formation and the internalization of Islamic values; formal education in schools and madrasahs functions to systematically structure knowledge and strengthen moral development; while nonformal education plays a role in reinforcing religious practices and habituating Islamic values in social life. The synergy among these three educational pathways forms a holistic and sustainable system of Islamic education, in which the family, school, and community function as integrated centers of education. Thus, the success of Islamic education is largely determined by effective collaboration among informal, formal, and nonformal education in responding to contemporary challenges.